Genotype × age interaction in human transcriptional ageing - Kent, J.; Göring, H.; Charlesworth, J.; Drigalenko, E.; Diego, V.; Curran, J.; Johnson, M.; Dyer, T.; Cole, S.; Jowett, J.; Mahaney, M.; Comuzzie, A.; et al. (2012)
Individual differences in biological ageing (i.e., the rate of physiological response to the passage of time) may be due in part to genotype-specific variation in gene action. However, the sources of heritable variation in human age-related gene expression profiles are largely unknown. We have profiled genome-wide expression in peripheral blood mononuclear cells from 1240 individuals in large families and found 4472 human autosomal transcripts, representing ~4349 genes, significantly correlated with age. We identified 623 transcripts that show genotype by age interaction in addition to a main effect of age, defining a large set of novel candidates for characterization of the mechanisms of differential biological ageing. We applied a novel SNP genotype × age interaction test to one of these candidates, the ubiquilin-like gene UBQLNL, and found evidence of joint cis-association and genotype by age interaction as well as trans-genotype by age interaction for UBQLNL expression. Both UBQLNL expression levels at recruitment and cis genotype are associated with longitudinal cancer risk in our study cohort.